169 The Effect of Standardized Ileal Digestible isoleucine:lysine in Diets Containing 20% Dried Distillers Grains with Solubles on Finishing Pig Performance and Carcass Characteristics - Clizer, David A (J Anim Sci, 2021)
Previous research suggests an increase of the isoleucine (Ile) requirement for late finishing pigs. Diets containing dried distillers grains with solubles (DDGS) provide excess leucine which can lead to changes in available Ile due to the antagonistic relationship of branched chain amino acids. Therefore, the Ile requirement in finishing diets containing DDGS deserve to be re-evaluated. A finishing study was conducted to determine the standardized ileal digestible (SID) Ile:Lysine (Lys) requirement in diets containing 20% DDGS. Pigs (n = 2,268; 82.3 ± 0.39 kgs) were used in a 56-d trial (14 replicates per treatment). Pens were assigned to one of six dietary treatments balancing for previous treatment. Treatments consisted of a corn-soybean meal diet (CS) or diets containing 20% DDGS with a SID Ile:lys ratio of 55, 60, 65, 70, or 75%. Data was analyzed as a randomized complete block, pair-wise comparisons and single degree of freedom orthogonal polynomials (DDGS diets only) were used to evaluate treatment responses, and pen was the experimental unit. Increasing the SID Ile:Lys did not impact cumulative performance of pigs fed diets containing 20% DDGS (P > 0.175). Pigs fed CS had improved (P < 0.010) ADFI compared to pigs fed SID Ile:Lys of 65 and 75% and tended (P = 0.084) to have greater ADG than 55 and 75% Ile:Lys treatments. Feed efficiency did not differ due to treatment (P = 0.427). Increasing the SID Ile:Lys to 65% in 20% DDGS diets decreased back fat and increased loin depth (quadratic; P < 0.029) and tended to increase percent lean (quadratic; P = 0.076), but did not alter hot carcass weight (P > 0.428). Pigs fed CS diets had greater hot carcass weights (P < 0.031) compared to pigs fed DDGS diets except for pigs fed 60% Ile:Lys diets. These data suggest a SID Ile:Lys of 60% is required to maximize growth performance and SID Ile:Lys of 65% increases carcass traits in diets containing 20% DDGS.